European bison (Bison bonasus) in the Chornobyl Exclusion Zone (Ukraine) and prospects for its revival - Gashchak, S.; Gulyaichenko, Y.; Beresford, N. A.; Wood, M. D. (Праці теріологічної школи, 2017)
In 2012–2016 a European bison adult bull was observed (by camera traps) in the Chornobyl Exclusion Zone (CEZ, Ukraine), west of Tovstyi Lis village. This is the first record of wild bison in Kyiv Polissya for over 300 years. The animal must have come from the Paliessie State Radioecological Reserve (PSRER, Belarus), having crossed the Pripyat river. The site where he was observed is 30–40 km from the locality where bison were introduced into the PSRER in 1996. The total area over which the bull has been observed is ca. 30–50 km2, and includes deciduous (oak, hornbeam, aspen) and mixed woodlands, and former grassy meadows now overgrown with birch, alder, aspen, pine. This constitutes the most favourable habitat type for bison available in the CEZ. The animal was only observed in February–March and August–October. Currently we are not able to judge how permanently the animal stays on this territory. Taking into account the amount of appropriate habitat in the region, size of the CEZ, protection regime and the fact that bison was a native species in the past, the CEZ could be the best area in Ukraine where a large free population of the European bison could be established. У 2012–2016 рр. за допомогою фотопасток спостерігали дорослого бика зубра у Чорнобильській зоні відчуження (ЧЗВ, Україна), західніше с. Товстий Ліс. Це перша реєстрація вільного зубра у Київському Поліссі за останні 300 років. Тварина мала прийти з Поліського державного радіоекологічного заповідника (ПДРЕЗ, Білорусь), перетнувши р. Прип’ять. Ділянка спостережень знаходиться у 30–40 км від місця, де зубрів інтродукували у ПДРЕЗ у 1996 р. Загальна її площа складає близько 30–50 км2 і включає широколистяні (дуб, граб, осика) і мішані ліси та колишні вологі луки, що зараз поросли березою, вільхою, осикою, сосною. Це найсприятливіші для зубра угіддя у ЧЗВ. Тварину спостерігали лише у лютому–березні та серпні–жовтні. Зараз бракує даних, щоб судити наскільки тварина постійно тримається ділянки. Приймаючи до уваги кількість угідь, що відповідають потребам зубра, розмір ЧЗВ, охоронний режим та той факт, що колись це був автохтонний вид, ЧЗВ могла б стати найкращим місцем в Україні, де можна було б створити велику вільну популяцію зубра.